Healing properties of epidermal growth factor and tocotrienol-rich fraction formulation in deep partial-thickness burn wound model - Guo, Hui-Fang (2017)
Burns are one of the most devastating injuries in the world, divided into superficial, partial-thickness (superficial or deep partial-thickness) and full-thickness burns. The current treatment of deep partial-thickness burns is mainly focused on preventing wound infections and less attention to the burn healing process. Therefore, it is imperative to develop medications aimed at promoting the stage of wound healing. It has been shown that epidermal growth factor (EGF) can promote the proliferation of various cells and it is known that tocotrienol-rich fraction (TRF) from palm oil has a strong antioxidant activity. Thus, a combination of EGF and TRF is included in the present formulation (EGF+TRF cream), which is expected to accelerate wound healing and inhibit oxidative stress in the burn. Deep partial-thickness burn wounds were produced on the dorsal part of Sprague-Dawley rats. Animals were then randomly divided into six groups: untreated, treated with Silverdin® cream, base cream, base cream with c% EGF, base cream with 3 % TRF or base cream with c% EGF and 3% TRF, respectively. Creams were applied once daily for 21 consecutive days. Digital images were captured daily for macroscopic evaluation. Six animals from each group were sacrificed on the 3rd, 7th, 11th, 14th and 21st day post-burn, harvesting skin tissues with the wound for histological, cellular, biochemical and gene expression analysis. Prior to the research of the EGF+TRF formulation in wound healing, a new apparatus was designed to create burn wounds. With this device, uniform deep partial-thickness burn was achieved with a contact temperature of 70°C, a fixed pressure of 300 g, and duration of 10 seconds. In addition, a novel histological scoring system was developed to make the evaluation process more systematic and reproducible. The chronological events in burn healing were initiated by the recruitment of neutrophils to the wound site on the 3rd day post-burn followed by the up-regulation of tumor necrosis factor-α (TNF-α) expression and rapid synthesis of collagens to facilitate leukocytes adhesion and crust attachment. The EGF+TRF treatment preceded this process and on the 7th day post-burn, wound contraction accelerated and the dermal healing was sped up by the proliferation of myofibroblasts and augmented expression of Collagen-1. By down regulation of interleukin 6 (IL-6) and TNF-α expression on Day 11 post-burn, the EGF+TRF treatment expedited the wound contraction and entering the re-modelling phase and arriving epithelialization on Day 14. This formulation was capable of promoting the recovery of the dermis and attenuate the oxidative stress by down regulating the expression of IL-6, TNF-α, inducible nitric oxide synthase (iNOS), matrix metalloproteinase-2 (MMP-2), tissue inhibitor of metalloproteinase-2 (TIMP-2), transforming growth factor-β1 (TGF-β1), vascular endothelial growth factor-A (VEGF-A) and Collagen-1. Finally, by Day 21 post-burn, the treatment of EGF+TRF formulation could advance the restoration of the epidermis and dermis and cut down the oxidative stress by down regulating the expression of IL-6 and iNOS. In conclusion, all results from the present study fully supported the beneficial application of EGF+TRF formulation in the treatment of deep-partial thickness burn, adhered to the mechanisms of burn healing process.